Analisis Pengaruh Bantuan Sosial PKH Dan Sembako Terhadap Tingkat Kesejahteraan Masyarakat Ditengah Pandemic Covid 19 Di Kabupaten Barito Utara - Arapah, Nor (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2020)
The purpose of this study was to analyze the effect of social assistance from the Family Hope Program and the Basic Food Program on the level of community welfare amid the COVID-19 pandemic in North Barito Regency. The Family Hope Program is assistance provided by the government to beneficiary families as a subsidy for household expenses for education and health. Meanwhile, the Sembako Program is food social assistance distributed in non-cash form from the Government to Beneficiary Families (KPM) every month through an electronic money mechanism. The basic food assistance program funds are used only to buy food items that have been determined for the Staple Food program in e-warong and cannot be collected in cash. Social Welfare is a condition for the fulfillment of the material, spiritual and social needs of citizens in order to live properly and be able to develop themselves so that they can carry out their social functions. The data used in this study are secondary data, while the analysis tool uses multiple linear regression. The analytical method used is Ordinary Least Square (OLS). The results showed that PKH and program assistance had a very significant effect (α = 1%) on improving the welfare of beneficiary households amid the COVID-19 pandemic in North Barito Regency.